The comparison of crude fat analysis between separated soxhlet method and one extractor soxhlet method for several feed ingredients - Sofyan Sofyan; Eneh Maesaroh; Ratih Windyaningrum; Brahmadhita Pratama Mahardhika (Labor Dasar dan Sentral Universitas Andalas, 2020)
Determination of crude fat content (ether extract) using a separate Soxhlet method requires an extraction time of 4 to 6 hours to achieve 5-6 circulation for 1 sample of material. Given the fact that the analysis and extraction time are not time efficient, therefore an alternative method is needed with good accuracy and faster testing time. One alternative is the single-extractor Soxhlet method. The aims of this study were to evaluate the comparison of crude fat extraction results in the separated Soxhlet method and the Soxhlet method in one extractor for several feed ingredients. For the fat testing, this study used two methods, namely the separate method and the Soxhlet method of testing single extractor. The experiments were done by a completely randomized design with 2 treatments and 3 replications. The data was analyzed using the Student T-test. The results showed that the separate Soxhlet method and the single extractor Soxhlet method had no significant difference to the crude fat content of the concentrate feed ingredients with T> 0.05. The use of single extractor Soxhlet showed significant result with T< 0.01 which lower ​​than the separate Soxhlet method in forage samples on the crude fat concentration. Given the outcomes, the use of single extractor Soxhlet is more efficient than the separate Soxhlet method in terms of analysis time of a large number of samples.